(untitled) (International Journal of Health, Animal Science and Food Safety, 2017)
Pecora dell’Amiata sheep is registered in the Regional population register of the autochthonous endangered sheep and goat breeds, and it is a double purpose breed (meat and milk). It derives from the mount Amiata area in Tuscany. In Tuscany the sheep meat consumption occurs in particular in Easter and in Christmas time. Because of the new markets, ewe meat has shown in the last years a consumption increase. In Italy, the more consumed ovine meat is the suckling lamb meat. In the last years, this kind of meat production and consumption decreased in Italy, but the ewe meat consumption has been slowly increased, because of the spread of typical regional food, and the new market needs. The trial was performed with ewes and lambs deriving from the local breed Pecora dell’Amiata. In this work, the Musculus longissimus dorsi (M. longissimus thoracis + lomborum) physical-chemical and nutritional characteristics of 23 ewes and 20 lambs were compared. The ewes of the trial were over 7 years old while the lambs were on average 80 days old. Ewe meat has shown lower drip loss (4.14 vs 2.71%) and lightness (L* 38.6 vs 45.3) values, and higher PH (6.15±0.07), shear force (8.4 vs 2.31 kg), fat content (5.9 vs 2.0%). The lamb meat lipids had higher polyunsaturated fatty acid content (PUFA: 14.58 vs 9.25%) and higher PUFA/Saturated Fatty Acids (SFA) ratio (0.31 vs 0.20). The PCA analysis identified two distinct groups regarding ewe and lamb meat respectively for the fatty acids composition and the health indices. Ewe meat showed dietetic and nutritional characteristics similar to that of lamb meat. These characteristics may allow in the future, to the ewe meat valorisation, now not appreciated by Tuscan and Italian market.